The ‘scorpion shrimp’, a new species of the genus Metapontonia (Crustacea: Decapoda: Palaemonidae) from Taiwan, with new generic record from Papua New Guinea - Ďuriš, Zdeněk; Lin, Chia-Wei (Zootaxa, 2016)
A new species of shrimp Metapontonia scorpio symbiotic with scleractinian coral Diploastrea heliopora is described from Taiwan. The species belongs to the smallest symbiotic shrimps of the family Palaemonidae. It is remarkable by a unique ability to turn its last two pleonites with tail fan dorsally over the 4th and preceding pleonal segments, thus resembling scorpions. For such movement, the respective opposing dorsal margins of the 4th–6th segments are deeply concave. The new species is characterized by a short dorsally directed rostrum, incomplete orbit, semicircular scaphocerite, and medially concave basal antennular segment. The only species of the genus, M. fungiacola, is compared with the new species based on morphology and DNA. Metapontonia fungiacola is for the first time reported from Taiwan and Papua New Guinea. The morphological and colour variability of the species is discussed. The scleractinian corals Platygyra lamellina (Merulinidae), Lobophyllia hemprichii, cf. Micromusa sp., Symphyllia cf. radians (Lobophylliidae), and Galaxea sp. (Oculinidae), are new host records for the species.